Marvin Redpost : a flying birthday cake? - Sachar, Louis, 1954-; Wummer, Amy (New York : Random House, 1999)
Two days after Marvin sees a glowing green thing like a flying birthday cake in the night sky, his third-grade class is joined by a mysterious new boy with peculiar behavior.
"A Stepping Stone book."
Horn Book Starred
Horn Book Starred, January 2000
3.6
3.6
3-6
Keywords: Extraterrestrial beings -- Fiction; Schools -- Fiction; Sleepovers -- Fiction; Aliens (Fictional characters) -- Fiction; School stories; Sleepovers -- Fiction